Assessment of the Economic Potential and Investment Attractiveness of the Dnipropetrovsk Region - Osadcha, N.; Zatyshniak, V. (Економічний вісник Донбасу, 2022)
The article analyzes the directions for Ukrainian economic recovery after the war. The successes stories of the countries, that restored their economies after the war, were explored. As a result the best practices of Israel seem most suitable for Ukraine. The methods of assessing the regions investment attractiveness are also described and adopted to evaluate the investment potential of the Dnipropetrovsk region. Nowadays, Dnipropetrovsk region is still the leader among the other Ukrainian regions in the production of industrial products and less suffered from the war than the other regions. We propose to use the Rasch model for the assessment of the regions' investment attractiveness for investors. Such assessment of Dnipropetrovsk, Kyiv, Kharkiv and Lviv regions was held within the framework of the study.